Endoscopic Surgery for Delayed Wound Healing After Achilles Tendon Suture Repair: A Report of Three Cases. Issue 3 (7th April 2021) - Yang, Yu‐ping; Chen, Hong‐yu; Cui, Guo‐qing; Xiu, Xiao‐lei; Liu, Xiao‐peng; An, Hua; Ao, Ying‐fang
Abstract : Background: Delayed wound healing is a potention complication after Achilles tendon suture repair and occurs for various reasons. The conventional treatment for delayed wound healing is open surgery, but patients face long recovery times and postoperative care is difficult. Case Presentation: This report presents three patients who were seen at our institute from April 2008 to October 2017 due to long‐term non‐healing wounds after surgery. All three patients had undergone surgery at least 2 months previously. We performed endoscopic surgery on these patients. After the operation, patients received less antibiotics and simpler care than would be required for conventional open surgery. There is no need to keep the wound open after the operation or perform wound cleaning for multiple times at the same time, which can reduce healing time. At the last follow up, all postoperative scores among the patients were significantly improved compared to before surgery. The Achilles tendon total rupture scores were excellent and the American Orthopedic Foot and Ankle Society scores were satisfactory, indicating improvements in Achilles tendon function and movement in patients after surgery. Conclusion: Our case reports demonstrate that arthroscopic treatment for delayed wound healing after Achilles tendon suture repair is satisfactory and reliable; frequent opening of the wound for cleaning is not required after the operation, thus reducing the healing time. Abstract : Delayed wound healing or poor healing is a potential complication after Achilles tendon suture repair. Non‐surgical methods are suitable for patients with mild symptoms, such as the use of sulfadiazine silver cream and negative pressure wound treatment. However, for patients who cannot be cured with non‐surgical treatments, the conventional treatment is open surgery. Debridement is used in surgery, and the wound is kept open for routine irrigation and dressing after the surgery until the tissue defect is repaired several days later. We pioneered the use of arthroscopy to treat patients with delayed wound healing after Achilles tendon suture repair. This article reports on three patients with delayed Achilles tendon wound healing who were treated with arthroscopy in our institution. We summarize our experience in treating the abovementioned patients and evaluate the advantages of arthroscopic treatment.